2019
DOI: 10.22159/ijpps.2019v11i11.35188
|View full text |Cite
|
Sign up to set email alerts
|

Development and Validation of Analytical Spectrophotometric and Rp-HPLC Methods for the Simultaneous Estimation of Hydroquinone, Hydrocortisone and Tretinoin Ternary Mixture in Topical Formulation

Abstract: Objective: Development and validation of spectrophotometric and RP-HPLC methods for the simultaneous determination of Hydroquinone (HQ), Hydrocortisone (HC) and Tretinoin (TRT) ternary combination in pharmaceutical preparation. Methods: The proposed spectrophotometric method was able to determine TRT directly from its absorption spectrum at 362 nm, however, HQ and HC from their first derivative spectra at 284 nm and 252 nm, respectively, without any separation step. The RP-HPLC method was developed using… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 10 publications
(7 reference statements)
0
4
0
Order By: Relevance
“…The proposed method validated as per the ICH guidelines [17] and USP Compendia [18] along with the references literature on method validation [19][20][21][22][23][24][25][26][27][28] studies in current industry practices.…”
Section: Resultsmentioning
confidence: 99%
“…The proposed method validated as per the ICH guidelines [17] and USP Compendia [18] along with the references literature on method validation [19][20][21][22][23][24][25][26][27][28] studies in current industry practices.…”
Section: Resultsmentioning
confidence: 99%
“…The proposed method validated as per ICH guidelines [20] and USP Compendia [21], along with references literature on method validation [12][13][14][15][16][17][18][19] studies in the current industry practices.…”
Section: Validation Of the Methodsmentioning
confidence: 99%
“…There is one harmonized method [11] of analysis that is published using high-performance liquid chromatography (HPLC) with charged aerosol detection technique. There was no other selective chromatographic method of analysis for simultaneous [12][13][14][15][16][17][18][19] determination of components of interest that was published in a unique HPLC method with ultraviolet detection. Hence, a method was developed and validated a high-performance liquid chromatographic technique with indirect ultraviolet detection for accurate and precise trace level determination of sodium chloride and sodium sulfate in SLS raw material using counter cation-exchange column.…”
Section: Introductionmentioning
confidence: 99%
“…Acne vulgaris is considered as common skin related problem that was treated with combination therapy using topical drug clindamycin and tretinoin (TTN) (1). Literature survey revealed that there is an evidence about the determination TTN by HPLC (2)(3)(4)(5)(6), RP-HPLC (7)(8)(9)(10)(11)(12), UPLC (13), LC (14), and GC (15). Studies on phototoxicity of tretinoin (16), UVspectrophotometry (17)(18)(19)(20)(21)(22), and UV-derivative spectroscopy (23)(24)(25) were also carried out by the previous authors.…”
Section: Introductionmentioning
confidence: 99%